Understanding the Support Needs and Challenges Faced by Family Caregivers in the Care of Their Older Adults at Home. A Qualitative Study - Hailu GN; Abdelkader M; Meles HA; Teklu T (Clinical Interventions in Aging, 2024)
Gebrezabher Niguse Hailu,1 Muntaha Abdelkader,1 Hailemariam Atsbeha Meles,2 Tesfay Teklu1 1Department of Nursing, Mekelle University, Mekelle, Tigrai Region, Ethiopia; 2Department of Health Informatics, School of Public Health, Mekelle University, Mekelle, Tigrai Region, EthiopiaCorrespondence: Gebrezabher Niguse Hailu, P.O.Box: 231, Tel +251991235149, Email gerigereking12@gmail.comBackground: As the global population ages, the demand for family caregivers is expected to increase, underscoring the necessity to comprehend their support needs and challenges they face. However, caregiving often comes with various challenges and support needs that require attention. This study was aimed to gain an in-depth understanding of the support needs and challenges faced by family caregivers who provide care to their elderly loved ones at home.Methods: The study was conducted in Mekelle City, Ethiopia from December 2022 to October 2023 using a phenomenology study design and purposive sampling technique. A total of twenty-two in-depth interviews were conducted using an open-ended guide. The interviews were transcribed verbatim, entered into ATLAS.ti8 software, translated, and analyzed using a thematic analysis.Results: The study found that family caregivers face communication, financial, medication management, and transportation challenges in caring for elderly relatives at home. It also highlighted several key support needs of family caregivers in the care of elderly relatives at home. These includes financial assistance, training, access to information, and support from healthcare professionals.Limitations: Qualitative research, by its nature, is subjective as it relies on the perceptions and interpretations of the participants. Moreover, in qualitative studies, researchers typically work with a limited number of participants, in qualitative studies, researchers typically work with a limited number of participants, resulting in conclusions that may not reflect the experiences of all family caregivers.Conclusion: This qualitative study underscored the multitude of challenges faced by family caregivers in their role as primary caregivers for elderly relatives. The research also highlighted the pressing need for support systems that would address the physical, emotional, financial, and informational needs of these caregivers.Keywords: family caregivers, older adults, support needs, challenges, home care, qualitative study